O APRENDIZADO DE HISTÓRIA A PARTIR DA INVASÃO DA INTERNET NA SALA DE AULA - CORREA, Rodrigo Cutrim (2024)
Currently, we are immersed in a scenario full of digital technologies, causing transformations in our ways of interacting, working, communicating and learning. These changes also directly interfere in the educational sphere, where Information and Communication Technologies (ICTs) enter the school environment. These technological resources have the potential to support pedagogical practices, encouraging students in the process of building historical knowledge. To better understand this new didactic process, in our dissertation we analyzed the use of Communication and Information Technologies (ICTs), especially the internet, as a way to teach history, considering the need for critical reflections and debates on the relationships between history and internet, public history and active methodologies. Basing our investigation on a theoretical-methodological approach to New Cultural History, qualitative research, with a descriptive approach, as well as bibliographic and documentary review, based on official research websites: Google Scholar, SciELO (Scientific Electronic Library Online) and CAPES (Coordination for the Improvement of Higher Education Personnel).